2014
DOI: 10.4236/ojpm.2014.45030
|View full text |Cite
|
Sign up to set email alerts
|

The Enjoyment of Physical Activity Determines Body Mass Index in Young People with Physical Disabilities

Abstract: Objective: This study aimed to 1) compare the body mass index (BMI) and patterns of out-ofschool activity participation in young people with and without physical disabilities, and 2) examine the relationship between BMI and the activity participation patterns among young people with physical disabilities. Methods: Thirty-nine young persons with physical disabilities (mean age ± standard deviation: 18.79 ± 1.99 years) and 70 healthy individuals (mean age ± standard deviation: 18.64 ± 0.74 years) participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Young people with disabilities come face to face with many obstacles that affect their PA, barriers that include a low level of self-esteem and motivation (Kozub, 2006), a lack of emotional support from family and friends, and environmental and structural limitations (Wrzesińska et al, 2018). In reality, young people with visual impairments find PA entertaining (Fong et al, 2014). In this study, the participants’ enjoyment of PA score was higher than average ( M : 55.1 ± 5.5), and a statistically significant and moderately positive correlation was found between the status of enjoying PA and the levels of PA ( r = 0.42; p < .01).…”
Section: Discussionmentioning
confidence: 99%
“…Young people with disabilities come face to face with many obstacles that affect their PA, barriers that include a low level of self-esteem and motivation (Kozub, 2006), a lack of emotional support from family and friends, and environmental and structural limitations (Wrzesińska et al, 2018). In reality, young people with visual impairments find PA entertaining (Fong et al, 2014). In this study, the participants’ enjoyment of PA score was higher than average ( M : 55.1 ± 5.5), and a statistically significant and moderately positive correlation was found between the status of enjoying PA and the levels of PA ( r = 0.42; p < .01).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, these high sedentary behaviours may have an adverse effect on their health, including their metabolic and cardiovascular systems (Taylor, 2014). Lower levels of physical activity participation have also been noted in other population groups of adolescents who experience a physical disability (Nooijen et al, 2014;Fong et al, 2014).…”
Section: Participation In Physical Activitymentioning
confidence: 99%
“…Enjoyment is a well-documented factor for determining physical activity participation (Fong et al, 2014). Engel-Yeger et al (2009) also found that the girls who experienced cerebral palsy (CP), in comparison to the able-bodied adolescents, were the group who reported the highest levels of enjoyment.…”
Section: Participation In Physical Activitymentioning
confidence: 99%